Medusa's stony stare : a retelling - Gunderson, Jessica; Pellegrino, Richard, 1980- (Mankato, MN : Picture Window Books, 2012)
An illustrated retelling of the Greek myth of Medusa, whose stare would turn any man to stone, and Perseus's quest to bring her head back to King Polydectes.
Includes bibliographical references (p. 32).
Horn Book
Library Media Connection starred
Horn Book, November 2012
Library Media Connection starred, March 2012
4.0
Keywords: Medusa (Greek mythology) -- Juvenile literature; Medusa (Greek mythology); Medusa (Greek mythology)